A critical evaluation of government-sponsored reviews of intellectual property in Australia - Endeshaw, A.; Sadler, Pauline (Routledge Taylor & Francis Group, 2012)
Constant changes to the Australian intellectual property (IP) system undertaken in the three decades since the 1970s have been accompanied by a proliferation of legislation and intermittent reviews. The staggering volume of such activities has generated debate as to whether such an approach should be allowed to continue in light of Australia's determination to forge ahead in knowledge creation and management that the information era demands. This article investigates the propriety and consistency of the reviews conducted, the respective recommendations made, and the underlying perspectives, if any, for IP lawmaking and implementation in Australia in the past or, indeed, for the future.